Effects on meat quality of Yerba mate (Ilex paraguariensis) in the diet of chickens - Bruna Barreto Przybulinski; Rodrigo Garófallo Garcia; Maria Fernanda de Castro Burbarelli; Sarah Sgavioli; Jean Kaique Valentim; Felipe Cardoso Serpa (Acta Scientiarum. Animal Sciences, 2023)
The objective is to evaluate the effects of the inclusion of yerba mate in the diet on the yield and quality of chicken meat stored frozen for 120 days after slaughter. The birds were distributed in a completely randomized design, with four treatments, and eight replications with 25 birds each. The treatments consisted of providing a basal diet with 1, 2, 4, and 6 g kg-1 of ground dehydrated Yerba mate. At slaughter, temperature, pH, and carcass yield were measured. 120 days after meat freezing, measurements of pH, colorimetry, cooking weight loss (CWL), shear force, and water retention capacity were estimated. The parameters evaluated after slaughter showed regression effects on breast and drumstick temperature. Breast temperature showed a decreasing linear effect (R2=0.61). For the variable thigh temperature, there was a negative quadratic effect (R2=0.66). The quality characteristics of breast and drumstick evaluated 120 days after freezing showed an increasing linear effect of drumstick CWL (R2=0.38). Yerba mate can be included in up to 6 g kg-1 in chicken feed without changing pH, color, and meat tenderness after 120 days of freezing, maintaining carcass and cut yields.